Local receptors as novel regulators for peripheral clock expression. Issue 11 (21st August 2014) - Wu, Changhao; Sui, Guiping; Archer, Simon N.; Sassone‐Corsi, Paolo; Aitken, Karen; Bagli, Darius; Chen, Ying
Abstract : Mammalian circadian control is determined by a central clock in the brain suprachiasmatic nucleus (SCN) and synchronized peripheral clocks in other tissues. Increasing evidence suggests that SCN‐independent regulation of peripheral clocks also occurs. We examined how activation of excitatory receptors influences the clock protein PERIOD 2 (PER2) in a contractile organ, the urinary bladder. PERIOD2:: LUCIFERASE‐knock‐in mice were used to report realtime PER2 circadian dynamics in the bladder tissue. Rhythmic PER2 activities occurred in the bladder wall with a cycle of ~24 h and peak at ~12 h. Activation of the muscarinic and purinergic receptors by agonists shifted the peak to an earlier time (7.2±2.0 and 7.2±0.9 h, respectively). PER2 expression was also sensitive to mechanical stimulation. Aging significantly dampened PER2 expression and its response to the agonists. Finally, muscarinic agonist‐induced smooth muscle contraction also exhibited circadian rhythm. These data identified novel regulators, endogenous receptors, in determining local clock activity, in addition to mediating the central control. Furthermore, the local clock appears to reciprocally align receptor activity to circadian rhythm for muscle contraction. The interaction between receptors and peripheral clock represents an important mechanism for maintaining physiological functions and its dysregulation may contribute to age‐related organ disorders.—Wu, C., Sui, G., Archer, S. N., Sassone‐Corsi, P., Aitken, K., Bagli, D., Chen, Y., Local receptors as novel regulators for peripheral clock expression. FASEB J. 28, 4610–4616 (2014). www.fasebj.org